Kajian Visualisasi Iklan Layanan Masyarakat “Sumpah Pemuda” - Tunjung Riyadi (Bina Nusantara University, 2011)
Watching television advertising means accepting the message and understand the meaning of the message from those impressions. With a fairly short duration, the audience is faced with the question of understanding various aspects. The first aspect is the accessibility to the senses of the eye and ear and continues to the senses understanding of meaning and sense and consideration. Semiotics is one approach to understanding television advertising where the ad itself as part of the marker system information. From the nature of information just to process an attempt